Preparation and Characterization of Carvedilol-Loaded Poly (D, L) Lactide Nanoparticles/Microparticles as a Sustained Release System - Majd Suleiman Mahmoud Bani-Odeh (My University, 2015)
Background: Polymeric nano and micro particles are promising delivery systems for the enhancement of the bioavailability of highly lipophilic drugs prone to ﬁrst pass metabolism. Purpose: This study aims at preparing carvedilol polymeric nanoparticles and microparticles with high loading efficiency. Other objective was to study carvedilol release profile from the obtained particles at room and body temperatures. Method: Carvedilol PDLLA nanoparticles and microparticles were prepared using nano-precipitation method. PVA was used as emulsifying agent. The effect of the solvents (acetone, tetrahydrofuran, acetonitrile, ethanol and dichloromethane) and the polymer amount on the size, size distribution and morphology of the formed particles were studied using atomic force microscope (AFM). Results: Spherical polymeric particles were obtained in all solvents used. The used method is easy, rapid, reproducible, effective (high loading capacity of carvedilol) and consequently can be used as new strategy for the development of carvedilol controlled release dosage forms. The in vitro release profile of carvedilol has shown a sustained release pattern with a little rapid release rate at body temperature in comparison to that at room temperature. Conclusion: The carvedilol loaded PDLLA nanoparticles have been successfully prepared with high loading efficacy and small particle size when acetone was used as the organic solvent and 12.5 mg of PDLLA polymer was used. Microparticles obtained when dichloromethane was used. The Korsmeyer Peppas with T lag model was the best one to explain the sustained release behavior.Chapter One

خلفية: الجزيئات النانو والمايكروبوليمرية هي من الأنظمة الواعدة في تسليم الأدوية بالجسم وتحسين توافرها الحيوي خصوصا الأدوية المحبة للدهون وشديدة العرضة للاستقلاب. الهدف: الهدف من الاطروحة هو تحضير جزيئات بوليمرية بحجم النانو وحجم المايكرو وتحميلها بدواء الكارفيدايلول بكفاءة عالية. والهدف الاخر ايضا هو دراسة خروج الدواء من الجزيئات بظروف مختلفة (على درجة حرارة الغرفة ودرجة حرارة الجسم). الطريقة: تم استخدام طريقة الترسيب في تحضير جزيئات النانو والمايكرو. تم استخدام نوع من البوليمر يدعى PDLLA. وتم استخدام بولي فينل الكحول للحصول على المستحلب لتحضير هذه الجزيئات. تم دراسة تأثير المذيبات (الأسيتون، رباعي هيدروفيوران، الأسيتونتريل، والإيثانول وثنائي كلورو ميثان) وكمية البوليمر على حجم وشكل الجزيئات المصنعة وتوزيعها الحجمي باستخدام جهاز AFM. النتائج: تم الحصول على جزيئات كروية الشكل في جميع المذيبات المستخدمة. الطريقة المستخدمة سهلة وسريعة وفعالة (سعة عالية التحميل من الكارفيديلول) وبالتالي يمكن استخدام استراتيجية جديدة لتطوير كارفيديلول بأشكال صيدلانية جديدة. وقد أظهرت التجربة المخبرية أن خروج الكارفيدايلول من الجزيئات على درجة حرارة الجسم اسرع مقارنة بخروجه على درجة حرارة الغرفة. الخلاصة: لقد تم تحضير جزيئات بحجم النانو والمايكرو باستخدام بوليمر PDLLA بكفاءة تحميل عالية، تم الحصول على أصغر الجزيئات باستخدام الاسيتون كمذيب عضوي وباستخدام 12.5 مليغرام من البوليمر المذكور. باستخدام ثنائي كلورو ميثان تم الحصول على جزيئات بحجم المايكرو. وظهر أن النمط المناسب لتفسير خروج الدواء المستدام من الجزيئات هو Korsmeyer with T lag.
تحضير وتوصيف الجزيئات البوليمرية بحجم النانو والمايكرو المحملة بدواء الكارفيدايلول كنظام تحرير دوائي مستدام